GROWTH OF Pinus glabra IN SOUTHERN BRAZIL - Dobner Jr., Mário; Nicoletti, Marcos Felipe; Novack Jr., Nilton Sergio; Nunes, Glaucia Cota (Floresta, 2019)
Species of the genus Pinus are widely cultivated in Brazil, in the south of the country, mainly P. taeda and P. elliottii are responsible for suppling for diverse industrial segments. Although poorly studied, other species from the same region of natural distribution could also possibly present good growth potential. The aim of the present study was to evaluate the development of different dendrometric characteristics of provenances of P. glabra grown in the highlands of south Brazil during 24 years of growth. The values obtained for P. glabra in the studied region was compared with the ones from its natural distribution region and with data of P. taeda in south Brazil. By means of annual dendrometric measurements during almost the entire studied period, especially at age 24 years, the growth and productivity of the species was addressed. All studied provenances shown suitability to the evaluated edaphoclimatic conditions, with initial height growth above 1 m year-1 during the first 5 years. Productivities above 30 m3 ha-1 year-1 at age 24 years, as well as the production of dominant individuals with 30 cm of dbh at age 15 years can be expected. Therefore, the potential for commercial use of P. glabra in the highlands of south Brazil was proven, thus being an interesting alternative to the commonly used species